The Relationships of Parental Alcohol Versus Tobacco and Marijuana Use With Early Adolescent Onset of Alcohol Use - Capaldi, Deborah M. (J Stud Alcohol Drugs, 2016)
OBJECTIVE: This study examined whether the use of tobacco and marijuana by fathers or mothers predicted onset of alcohol use in their offspring over and above effects of parental alcohol use. METHOD: The present study included 146 children of 93 parents (90 fathers and 85 mothers). The fathers were originally recruited as boys to the Oregon Youth Study, a study of community, familial, and individual risk factors for delinquency. RESULTS: Only mothers’ but not fathers’ alcohol use was associated with children’s age at onset. Children’s age at onset was predicted by mothers’ tobacco use and by the interaction of fathers’ marijuana use and alcohol use. These effects were observed when controlling for parental education, child’s gender, and also child’s antisocial behavior—a general developmental risk factor for substance use onset in adolescence. CONCLUSIONS: Mothers’ substance use played a major role in childhood onset of alcohol use, yet the role of maternal substance use as a risk factor for their children has previously received less attention than the role of paternal substance use. Also, findings imply that it may be important to identify children of polysubstance-using parents for targeted prevention programs.